(untitled) (Homoeopathy for All, 2025)
Modernizing Homoeopathy Edu cation: The WHO GTM Strategy 2025–2034 calls for regulated, cul turally sensitive education across Traditional Medicine systems. Despite its presence in over 100 countries, Homoeopathy lacks consistent educational standards— highlighting the need for globally aligned standards. Establish Global Educational Benchmarks: Dedicated guide lines for homoeopathy will raise educational quality, strengthen reg ulatory frameworks, and enhance clinical credibility. These bench marks can support diverse educa tional models worldwide. Integrate Interdisciplinary & Complementary Systems: Aligned with Hahnemannian philosophy, Homoeopathic curricula should incorporate relevant knowledge and competencies from other TM —Ayurveda, Anthroposophy, Yoga and Naturopathy—along with nutrition, counselling, and mind– body therapies. Mobilize Support from Member States and Stakeholders : Member states should be motivated to include homoeopathy in health policies, initiate global academic dialogue, and adopt adaptable standards that reflect cultural and healthcare diversity. Embed Sustainability Across Academic, Cultural & Systemic Layers: Build resilience through clinically relevant programs, local engagement, and alignment with national healthcare strategies—re specting indigenous and biomedical knowledge and ecological values. Position India as a Global Leader: Indian institutions should champion innovation and global collaboration—through tailored programs, faculty exchange, and knowledge-sharing—to establish India as a homoeopathic education and research leader.